Suppression of a lethal trisomic phenotype in Drosophila melanogaster by increased dosage of an unlinked locus. - Dorer, D.R.; Cadden, M.A.; Gordesky-Gold, B.; Harries, G.; Christensen, A.C. (Genetics, 1993)
One of the most extreme examples of gene dosage sensitivity is the Triplo-lethal locus (Tpl) on the third chromosome of Drosophila melanogaster, which is lethal when present in either one or three copies. Increased dosage of an unlinked locus, Isis, suppresses the triplo-lethal phenotype of Tpl, but not the haplo-lethal phenotype. We have mapped Isis to the X chromosome region 7E3-8A5, and shown that the suppression is a gene dosage effect. Altered dosage of Isis in the presence of two copies of Tpl has no obvious effects. By examining the interactions between Isis dosage and Tpl we suggest that Isis does not directly repress Tpl expression, but acts downstream on the triplo-lethal phenotype of Tpl.